The complete chloroplast genome sequence of Moringa oleifera Lam. (Moringaceae). Issue 2 (3rd July 2019) - Lin, Wen; Dai, Seping; Chen, Yile; Zhou, Yubin; Liu, Xiaojuan
Abstract: The plant family Moringaceae contains only one genus, Moringa, and Moringa oleifera is widely cultivated for its young seed pods and leaves used as vegetables and for traditional herbal medicine. In this study, we report the complete chloroplast genome of M. oleifera, assembled from whole-genome high-throughput sequencing reads, as a resource for future studies on the phylogeny and evolution of Moringaceae. The chloroplast genome was 160, 600 bp in length, with a large single-copy (LSC) region of 88, 577 bp, a small single-copy (SSC) region of 18, 883 bp, separated by two inverted repeat (IR) regions of 26, 570 bp each. It was predicted to contain 131 genes, with an overall GC content of 36.78%. Phylogenetic analysis of 71 protein-coding sequences of 13 plant plastomes showed that M. oleifera is closest to Carica papaya .